Development of a periplasmic FRET screening method for protease inhibitory antibodies. Issue 11 (6th June 2013) - Nam, Dong Hyun; Ge, Xin
ABSTRACT Proteases play critical roles in numerous physiological processes and thus represent one of the largest families of potential pharmaceutical targets. Previous failure of broad‐spectrum small molecule inhibitors toward tumorigenic metalloproteinases in clinical trials emphasizes that selectivity is the key for a successful protease‐inhibition therapy. With exquisite specificity, antibody‐based inhibitors are emerging as promising therapeutics. However, the majority of current antibody selection technologies are based on binding and not on inhibition. Here, we report the development of a function‐based inhibitory antibody screening method, which combines a simple periplasmic preparation and an ultra sensitive FRET assay, both processes are amenable to high‐throughput applications. Using this method, inhibitory antibodies can be rapidly distinguished from non‐inhibitory clones with satisfactory Z‐factors. Coupled with ELISA, this method also provides a fast semi‐quantitative estimation of IC50 values without antibody purification. We expect this technology to greatly facilitate the generation of highly selective biologic inhibitors, targeting many proteases that are important to medical research and therapeutic development. Biotechnol. Biotechnol. Bioeng. 2013;110: 2856–2864. © 2013 Wiley Periodicals, Inc.